2017
DOI: 10.5194/acp-2017-1143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the effect of mixing on the mean Age of Air in CCMVal-2 and CCMI-1 models

Abstract: Abstract. Stratospheric age of air (AoA) is a useful measure of the overall capabilities of a general circulation model (GCM) to simulate stratospheric transport. Previous studies have reported a large spread in the simulation of AoA by GCMs and coupled chemistry-climate models (CCMs). Compared to observational estimates simulated AoA is mostly too low. Here we attempt to untangle the processes that lead to the AoA differences between the models and between models and observations. AoA is influenced by both… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…the mean from ) the values range between 5.52 years in the MRI model and 3.18 years in the ACCESS model simulation. This topic had already been discussed for example in SPARC (2010) and in Dietmüller et al (2018). Analysing the hindcast simulations of the CCMVal-2 and the CCMI-1 projects, Dietmüller et al (2018) showed that it is mainly the mixing rather than the residual circulation that causes the large AoA spread and that this is likely linked to the different resolutions of the model simulations.…”
Section: Changes In Aoa and In Its Componentsmentioning
confidence: 93%
See 4 more Smart Citations
“…the mean from ) the values range between 5.52 years in the MRI model and 3.18 years in the ACCESS model simulation. This topic had already been discussed for example in SPARC (2010) and in Dietmüller et al (2018). Analysing the hindcast simulations of the CCMVal-2 and the CCMI-1 projects, Dietmüller et al (2018) showed that it is mainly the mixing rather than the residual circulation that causes the large AoA spread and that this is likely linked to the different resolutions of the model simulations.…”
Section: Changes In Aoa and In Its Componentsmentioning
confidence: 93%
“…We therefore calculate the mixing efficiency, an independent measure for the relative strength of mixing for given residual mean transport changes (ratio of mixing mass flux to net mass flux) (Garny et al, 2014), across the 21st century by means of a one-dimensional transport model of the stratosphere in the CCMI-1 model simulations. In the companion paper, Dietmüller et al (2018) have already shown that the mixing efficiency can explain most of the climatological AoA model spread. In the present study, we quantify the impact of mixing efficiency (relative mixing strength) differences in individual model simulations.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations